Proposal of a single‐phase synchronous inverter with noninterference performance for power system stability enhancement and emergent microgrid operation. Issue 3 (13th May 2019) - Sekizaki, Shinya; Yorino, Naoto; Sasaki, Yutaka; Matsuo, Kosuke; Nakamura, Yuki; Zoka, Yoshifumi; Shimizu, Toshihisa; Nishizaki, Ichiro
Abstract: A novel design of a single‐phase synchronous inverter (SSI) having noninterference core dynamic performance is proposed, referred to as noninterference core SSI (NIC‐SSI) in this paper. The proposed inverter consists of "core" and "shell." This novel design is advantageous for a flexible setting of the core controller to enhance power system stability, which is supported by the shell function for keeping robust synchronizing operation of inverters including microgrid operation. The novel points in this paper are summarized as: (a) the proposed controller enables SSIs to implement directly a desired dynamic characteristic such as a synchronous machine; (b) it can connect any single‐phase systems as well as three‐phase systems; (c) an islanded single‐phase microgrid without rotating machines can be stabilized by multiple SSIs. The proposed controller makes it possible to enhance system stability against increasing uncontrollable renewable energy sources (RESs) and static power conversion devices. The developed SSI realizes flexible use in the demand side operations under normal/faulted grid conditions. Hardware‐in‐the‐loop (HIL) testbed including the proposed digital controller and the real‐time simulator validates the effectiveness of the proposed controller in the experimental conditions.